The potential for CXCL13 in CSF as a differential diagnostic tool in central nervous system infection. Issue 9 (1st September 2020) - Masouris, Ilias; Klein, Matthias; Ködel, Uwe
ABSTRACT: Introduction : Central nervous system (CNS) infections can be life-threatening and are often associated with disabling sequelae. One important factor in most CNS infections is a timely pathogen-specific treatment. The diagnostic methods available, however, do not always reach a satisfying sensitivity and specificity. In these cases, there is need for additional diagnostic biomarkers. Chemokines represent potential candidates as biomarkers, since they are an important pillar of the host immune response. The aim of this review is to discuss the diagnostic potential of cerebrospinal fluid (CSF) CXCL13 in patients with CNS infections. Areas covered : Data were obtained from a literature search in PubMed up to October 2019. This review focusses on articles on the potential of CXCL13 as a diagnostic tool. The majority of identified studies aimed to characterize its role in two diseases, namely Lyme neuroborreliosis and neurosyphilis. Expert opinion : CSF CXCL13 has a significant potential as a diagnostic and monitoring add-on marker in Lyme neuroborreliosis. Differences in study design, control groups and clinical parameters between studies, however, affect sensitivity, specificity and cutoff values, underlining the need of further studies to address these issues and pave the way for a generalized clinical practice.